DAMPAK STEREOTIP MEDIA SOSIAL X TERHADAP INTERAKSI SOSIAL DAN PERILAKU GENERASI Z - Maulida, Aisyah Ichsani; Amandy, Rafa Dahayu; Tri Novitasari, Rizqi; Ridho, Kholis (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
Generation Z is a generation that has grown up with digital technology as an integral part of their lives. The main focus of this study is the impact of stereotypes spread through social media on the social interactions and behaviors of this generation. Using a questionnaire-based survey method, data was collected from 100 Generation Z respondents who are active on social media X. The results showed that social media X has a role to play in the social interaction and behavior of this generation. The results showed that social media X has an important role in Generation Z's communication, selfexpression and social awareness. Respondents recognized the benefits of social media in opening up insights into social issues and diversity, although the stereotypes circulating are not always accurate. In addition, social media is also considered capable of countering negative stereotypes through positive content that supports identity and diversity. However, respondents still see in-person interaction as an important element in building deeper relationships. In conclusion, social media X is not only a tool to enhance Generation Z's social connections and confidence, but also plays a role in reducing the negative impact of stereotypes through wise use